2015
DOI: 10.3168/jds.2015-9409
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calving in the summer on the hepatic transcriptome of Holstein cows during the peripartal period

Abstract: The liver is the main metabolic organ coordinating the adaptations that take place during the peripartal period of dairy cows. A successful transition into lactation, rather than management practices alone, depends on environmental factors such as temperature, season of parturition, and photoperiod. Therefore, we analyzed the effect of calving season on the hepatic transcriptome of dairy cows during the transition period. A total of 12 Holstein dairy cows were assigned into 2 groups based on calving season (6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…During early lactation, gluconeogenesis and glycogenolysis are typically increased to provide glucose for milk lactose production [ 18 , 19 ]. The increase in gluconeogenesis is much more pronounced in cows calving during a hot summer as compared to a cold spring period [ 20 ] and presumably involves increased utilization of lactate and alanine for glucose synthesis [ 20 , 21 ]. Furthermore, hepatic mRNA expression of genes encoding fatty acid oxidation increases during the transition period from late pregnancy into lactation [ 18 , 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During early lactation, gluconeogenesis and glycogenolysis are typically increased to provide glucose for milk lactose production [ 18 , 19 ]. The increase in gluconeogenesis is much more pronounced in cows calving during a hot summer as compared to a cold spring period [ 20 ] and presumably involves increased utilization of lactate and alanine for glucose synthesis [ 20 , 21 ]. Furthermore, hepatic mRNA expression of genes encoding fatty acid oxidation increases during the transition period from late pregnancy into lactation [ 18 , 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hepatic mRNA expression of genes encoding fatty acid oxidation increases during the transition period from late pregnancy into lactation [ 18 , 19 , 22 ]. When cows, however, experience heat during the transition period, expression of genes associated with fatty acid oxidation is downregulated compared to control counterparts [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found increased abundance of PC protein during pp heat stress, suggesting activated gluconeogenesis. In line with this, Shahzad et al (Shahzad et al 2015) reported a greater PC mRNA abundance in transition cows with summer compared to winter calving, although this might be due to the lower feed intake as well. However, lactating cows adapt to heat by increasing carbohydrate utilization (Rhoads et al 2009, Lamp et al 2015), and increased gluconeogenesis may meet these increased glucose requirements.…”
Section: Discussionmentioning
confidence: 64%
“…Glycans are carbohydrates linked with lipid and protein moieties to form glycolipids and glycoproteins that can act as signaling molecules [34]. Despite previous work with dairy cows [7, 19, 35] demonstrating substantial changes in several glycan-related pathways in liver tissue during the transition period, not much attention has been placed on glycan metabolism. However, a review of the literature highlighted that there has been a marked increase in glycomic studies in humans [36], highlighting their importance.…”
Section: Resultsmentioning
confidence: 99%